2014
DOI: 10.1007/s11250-014-0544-2
|View full text |Cite
|
Sign up to set email alerts
|

Predatory capability of the nematophagous fungus Arthrobotrys robusta preserved in silica gel on infecting larvae of Haemonchus contortus

Abstract: Biological control of gastrointestinal nematodiasis in ruminants is an alternative to reduce the number of infective larvae. The fungal isolates predatory activity preservation is a basic requirement for the success of this control type. The aim of this work is to evaluate the predatory capacity of the fungus Arthrobotrys robusta (isolate I-31), preserved on silica gel on infective larvae of Haemonchus contortus under laboratory conditions on 2 % water agar (2 % WA). In this essay, A. robusta storage on silica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…However, as previously mentioned, the culture medium serves not only for fungal growth, but also as a "modulator" of enzymatic production. For example, rich casein-based media produce a greater quantity of proteases and chitin-based media produce a greater quantity of chitinase (Soares et al, 2013, Braga et al, 2014. Braga et al (2015) reported the production of extracellular enzymes, chitinases, by the fungus D. flagrans, in the presence of nematodes, suggesting that the infection is due to the fact that the eggs of the nematodes are rich in chitin.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, as previously mentioned, the culture medium serves not only for fungal growth, but also as a "modulator" of enzymatic production. For example, rich casein-based media produce a greater quantity of proteases and chitin-based media produce a greater quantity of chitinase (Soares et al, 2013, Braga et al, 2014. Braga et al (2015) reported the production of extracellular enzymes, chitinases, by the fungus D. flagrans, in the presence of nematodes, suggesting that the infection is due to the fact that the eggs of the nematodes are rich in chitin.…”
Section: Resultsmentioning
confidence: 99%
“…The use of nematophagous "eating" fungi has been widely studied and in recent years, it has been found that growing these nematophagous fungi in chitin-based culture media could "mold" their predatory activity for combatting arthropods, demonstrating the use of chitin as a source of nutrition (Braga et al, 2013). On the other hand, some fungi that previously only destroyed infective larvae of helminth gastrointestinal parasites may very well produce extracellular enzymes such as chitinases, which promote the destruction of the exoskeletons of arthropods (Soares et al, 2014). The aim of this study was to evaluate the interaction and activity of nematophagous fungus D. flagrans on H. irritans (Diptera: Muscidae) in Nelore cattle in the Southeast region of Brazil.…”
Section: Introductionmentioning
confidence: 99%
“…For use in biocontrol program as for survival and dissemination in environment condition of fungal spores is necessary [ 13 ] and when it comes to parasites animal control is important to select species and/or isolates capable of crossing the digestive tract and maintain the viability and predatory ability [ 16 ]. Thus, the objective of this study was to assess antagonism of nematophagous fungi and species producers metabolites and their effectiveness on L 3 of H. contortus .…”
Section: Introductionmentioning
confidence: 99%